Coping with the suicide of a loved one - Ellis, Albert, 1913-2007; Institute for Rational-Emotive Therapy; Baxley Media Group (New York, NY : RET-BMG, 1993)
Psychotherapist Albert Ellis identifies the cognitive-emotive connection, the process of debating a client's self-defeating internal dialogue and shows how to incorporate role-playing in the therapy. Shows models of psychotherapy sessions to illustrate how therapists apply rational-emotive therapy (RET) to their personal styles
Title from title screen
Psychotherapist: Albert Ellis
Keywords: Rational emotive behavior therapy; Suicide -- psychology; Cognitive therapy